The Bronze Age fortresses of the Southern Urals - Semyan, Ivan (ARAMAZD: Armenian Journal of Near Eastern Studies, 2023)
The archaeology of the steppes of the Southern Urals is known in world science due to the phenomenon of large fortified settlements. The Sintashta archaeological culture created a unique economic model based on settled pastoralism and advanced metallurgy. To control the resources, large fortified settlements were built, which had an unusually high concentration of population for the steppe. Archaeological finds demonstrate a high level of military development. With all this, agriculture was unknown to the ancient Indo-Europeans of the Southern Urals. This article discusses the emergence, transformation and extinction of the tradition of fortification in the Bronze Age in the Southern Urals. The author gives examples of the most well-studied fortified settlements, as well as describes the history of scientific views on the phenomenon and the main modern approaches to the study. On the basis of numerous archaeological data obtained with the help of modern research methods, the author of the article and the artist-reconstructor recreated the appearance of the fortified settlement of Kamennyi Ambar in the Sintashta era. The general appearance, the scheme of the defensive wall and ditch, as well as the possible appearance and construction of the fortified entrance are recreated. Based on the available archaeological data, the author concludes that the Sintashta fortification is an important marker of developed social complexity and had great defensive potential in the Southern Urals of the Bronze Age.